2007
DOI: 10.1088/0022-3727/40/18/s10
|View full text |Cite
|
Sign up to set email alerts
|

Tribo-corrosion of coatings: a review

Abstract: This paper reviews the available literature relating to the emerging research into the performance of coatings under combined wear and corrosion conditions. Understanding how coatings perform under these tribo-corrosion conditions is essential if the service life of equipment is to be predicted and to allow service life to be extended. Therefore, the tribo-corrosion performance of coatings deposited by a variety of techniques is discussed and the main mechanisms associated with their degradation under combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(95 citation statements)
references
References 100 publications
1
94
0
Order By: Relevance
“…There are no significant difference in the evolution of friction coefficient at different loads and as in the previous case, did not show a definite pattern in the variation. Further, in the previous study it was shown that friction coefficient values might increase or decrease, associated with the decrease and/or fluctuations in corrosion current, which is exhibiting the complexity of such dynamic tribocorrosion systems [10,16].…”
Section: Evolution Of Friction Coefficient As a Function Electrode Pomentioning
confidence: 92%
See 1 more Smart Citation
“…There are no significant difference in the evolution of friction coefficient at different loads and as in the previous case, did not show a definite pattern in the variation. Further, in the previous study it was shown that friction coefficient values might increase or decrease, associated with the decrease and/or fluctuations in corrosion current, which is exhibiting the complexity of such dynamic tribocorrosion systems [10,16].…”
Section: Evolution Of Friction Coefficient As a Function Electrode Pomentioning
confidence: 92%
“…Recently Wood et al [10] reviewed the tribo-corrosion studies of the coatings and films. The general corrosion/tribo-corrosion behaviour of ZrC x O y and TiC x O y films in the presence of artificial perspiration solution was studied [4][5][6][7][8][9] and other work has investigated synergistic effects between corrosion and wear for the purpose of generating tribocorrosion maps for thermally sprayed coatings [11].…”
mentioning
confidence: 99%
“…Since the long-term durability of the prosthetic joint materials rely on the successful control of both the corrosion that produces ions release and the tribocorrosion resistance that produces ions release and oxide or plastic debris, Physical Vapor Deposition (PVD) multilayer coatings offer a multifunctional protection alternative and good adherence to metallic substrates in comparison to the monolayer coating [15,[21][22][23][24][25][26]. The multilayer combine the properties of different materials in a single protective layer.…”
Section: Introductionmentioning
confidence: 99%
“…This multi functional coating would then resist both corrosion, wear and provide a low coefficient of friction [113,117]. This would increase the lifetime of many engineering applica tions, and for example, increase the fuel efficiency of ve hicles since it reduces energy losses due to friction.…”
Section: Multifunctional Coatingsmentioning
confidence: 99%
“…7. In a recent review by Wood [117] it is clear that this is a research area that re quires significant attention in the future.…”
Section: Multifunctional Coatingsmentioning
confidence: 99%